Study of influence of quadrocopter design and settings on quality of its work during monitoring of ground objects - Maidanyk, Oleksandr; Meleshko, Yelyzaveta; Shymko, Serhii (Національний технічний університет "Харківський політехнічний інститут", 2021)
The subject of the article is methods of reducing quadcopter magnetometer crosstalk by changing the design and settings of the copter to improve the quality of its work during the monitoring of ground objects. The relevance of the development is determined by the need to increase the physical safety of quadcopters when monitoring ground facilities in various industries because the magnetometer is the most noise-sensitive sensor, and its failure leads to the fall and loss of the drone. The purpose of the article is to determine the optimal design and settings of the quadcopter in terms of its physical safety and quality of work during monitoring of ground facilities in various industries. The research task is to check whether it is possible to protect the magnetometer placed inside the drone body from the power cables crosstalk by grounding, shielding and changing the initial settings of the copter, namely by changing the value of the startup power factor of the motors. Research methods are as follows: theory of automatic control, methods of optimal control and hardware design methods. Conclusions. The role of the drone magnetometer in the monitoring of ground objects has been studied. The study has shown that copters at monitoring ground objects must be equipped with a magnetometer and GPS. The magnetometer is the most sensitive to interference of all sensors. If it does not work properly, the entire drone navigation system stops working. We have carried out experimental studies of the influence of quadcopter design and settings on the quality of its magnetometer work, and hence on work of the copter as a whole. In this paper it is proposed to place a magnetometer inside the body of the drone that will increase its physical safety and simplify the design of the drone, but at the same time it will increase the coupling from the power cables of motors, so it is necessary to choose effective methods of protection. It has been tested whether it is possible to protect the magnetometer from interference from power cables when placing it inside the drone body by grounding, shielding and changing the initial settings of the copter, namely by changing the value of the startup power factor of the motors. The results of the experiments showed that to protect against the interference for magnetometer placed inside the drone body, it is necessary to combine shielding of the magnetometer and decreasing of the startup power factor of the motors.

Предметом вивчення у статті є методи зменшення наведень на магнітометр квадрокоптера за рахунок зміни конструкції та налаштувань коптера для підвищення якості його роботи при моніторингу наземних об'єктів. Актуальність розробки визначається необхідністю підвищення фізичної безпеки квадрокоптерів при моніторингу наземних об'єктів у різних галузях виробництва, адже, магнітометр є найбільш чутливим до шумів датчиком, а його вихід з ладу призводить до падіння та втрати дрону. Метою є визначення оптимальної конструкції та налаштувань квадрокоптера з точки зору його фізичної безпеки та якості роботи при моніторингу наземних об'єктів у різних галузях виробництва. Завдання: перевірити чи можна захистити магнітометр при розміщенні його всередині корпусу дрону від завад з кабелів електроживлення заземленням, екрануванням та зміною стартових налаштувань коптера, а саме зміною значення коефіцієнту пускової потужності двигунів. Методи досліджень: теорія автоматичного управління, методи оптимального управління та методи проектування апаратного забезпечення. Висновки. Проведено дослідження ролі магнітометра дрону при моніторингу наземних об'єктів. Дослідження показало, що коптери, які здійснюють моніторинг наземних об'єктів, обов'язково повинні бути оснащені магнітометром та GPS. Магнітомер найбільш чутливий до перешкод датчик. Якщо він працює неправильно, перестає працювати вся навігаційна система дрону. Проведено експериментальні дослідження по впливу конструкції та налаштувань квадрокоптера на якість роботи його магнітометра, а одже і коптера в цілому. У даній роботі запропоновано розмістити магнітометр всередині корпусу дрона, що підвищить його фізичну безпеку та спростить конструкцію дрону, але разом з тим на нього збільшуються завади від кабелів електроживлення двигунів, тому необхідно підібрати ефективні методи захисту від таких завад. Перевірено чи можна захистити магнітометр при розміщенні його всередині корпусу дрону від завад з кабелів електроживлення заземленням, екрануванням та зміною стартових налаштувань коптера, а саме зміною значення коефіцієнту пускової потужності двигунів. Результати проведених експериментів показали, що для захисту від завад магнітометра, розміщеного всередині корпусу дрона, необхідно поєднати екранування магнітометра та зменшення коефіцієнту пускової потужності моторів.
Дослідження впливу конструкції та налаштувань квадрокоптера на якість його роботи при моніторингу наземних об'єктів
Keywords: unmanned aerial vehicle; drone; magnetometer; crosstalk; безпілотний літальний апарат; дрон; магнітометр; наведення